Evaluasi implementasi program rujuk balik (PRB) di Puskesmas Kota Semarang - Karti, Indah Mayang; Priyatni, Nunung; Hendra, Phebe (Poltekkes Kemenkes Aceh, 2025)
Background: The Referral Back Program (PRB) is a strategy of the Indonesian Health Insurance Agency (BPJS Kesehatan) to transfer the management of chronic disease patients from hospitals to community health centers in order to reduce referral burdens, improve efficiency, and maintain continuity of therapy. Its implementation still faces limitations in resources, suboptimal coordination, and low patient compliance, thus requiring a comprehensive evaluation to assess the program's effectiveness.Objective: This study aims to evaluate the implementation of the Referral Back Program (PRB) by reviewing the input, process, and output aspects of PRB implementation in community health centers in Semarang City in 2024.Method: This study is a descriptive qualitative study conducted in 10 pilot project community health centers in Semarang City in 2024. Data were collected through observation, in-depth interviews, and document studies. Respondents consisted of health center heads, health workers, PRB administrative staff, and PRB patients. Data analysis was performed using triangulation of sources, methods, and documents.Results: The implementation of PRB at the Semarang City Health Center in 2024 was not optimal. In terms of input, there was a shortage of health workers, uneven distribution of medicines, and manual administration. In terms of service implementation, guidelines were followed, but coordination between FPKTP and FPKTL was inconsistent and patient education was not structured. In terms of output, patient compliance was still low, program effectiveness was not optimal, and patient satisfaction was influenced by the availability of medicines and the smooth running of services.Conclusion: PRB at the Semarang City Health Center has not been effective due to limited resources, weak coordination, and low patient compliance. This condition shows a gap between policy and practice, so it is necessary to strengthen human resources, improve administration, increase coordination, and educate patients to support the success of PRB.